Converting coals into carbon-based pH-universal oxygen reduction catalysts for fuel cells. (1st February 2021) - Qi, Jiawei; Jin, Bolin; Liu, Weiqi; Zhang, Wendu; Xu, Lang
Graphical abstract: Highlights: Coals are utilized as resources and transformed into advanced fuel cell catalysts. Metal-free N-doped carbons are prepared successfully by a solid-state strategy. Coal-based carbons are applied to pH-universal ORR catalysts for the first time. Coal-based carbons own comparable ORR activity with Pt/C in a wide pH range. Etching degree and annealing temperature affect structures and catalytic activity. Abstract: Tapping into the potentialities of coals as valuable resources that can be transformed into state-of-the-art energy-related materials is now a burgeoning and fascinating research area, which accords with the clean utilization of coals. In the present work, coal-based porous nitrogen-doped carbon (CPNC) electrocatalysts toward the oxygen reduction reaction (ORR) at fuel cell cathodes have been easily prepared by the mechanochemistry-assisted strategy. Catalyst preparation combines the low-temperature pyrolysis with the high-temperature annealing, which guarantees nitrogen-containing substances sealed and confined in the carbon layers and skeletons and effectively converts them into nitrogen-relevant bonds, simultaneously regulating architectural features ( e.g. specific surface areas, pore width distributions, defects and edges). The optimal metal-free CPNC electrocatalyst owns onset potentials of 0.97, 0.80 and 0.87 V, half-wave potentials of 0.84, 0.64 and 0.65 V, limiting current densities of 4.96, 4.60 and 4.90 mA cm −2, electron-transfer numbers of 3.93, 3.92 and 3.91, together with fine current stability and methanol tolerance, in 0.1 M KOH, 0.5 M H2 SO4 and 0.1 M phosphate buffer solution (pH = 7.0), respectively. This is the first report on high-performance coal-based pH-universal oxygen reduction electrocatalysts, attributed to the effective trade-off between textural properties of catalysts (related to surface areas and pore structures) and the number of catalytic reaction sites (associated with nitrogen configuration distributions). Accordingly, this work has established the basis by which earth-abundant coals are readily converted into high-performance oxygen reduction carbonaceous electrocatalysts that are able to be integrated into various fuel cell test beds.